2010
DOI: 10.1093/nar/gkq1160
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory modules function in a non-autonomous manner to control transcription of the mbp gene

Abstract: Multiple regulatory modules contribute to the complex expression programs realized by many loci. Although long thought of as isolated components, recent studies demonstrate that such regulatory sequences can physically associate with promoters and with each other and may localize to specific sub-nuclear transcription factories. These associations provide a substrate for putative interactions and have led to the suggested existence of a transcriptional interactome. Here, using a controlled strategy of transgene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 59 publications
6
26
0
Order By: Relevance
“…MBP transcription is regulated by 4 enhancers localized in the first 10 kb of the mbp 5 0 -flanking sequence. One of the enhancers can enhance the transcription of both mbp and golli-mbp genes [51]. Although it has not been localized, the expression pattern of the MBP-CCL2 transgene that we observe is thus consistent with integration at a site(s) controlled by a Gollimbp enhancer.…”
Section: Discussionsupporting
confidence: 70%
“…MBP transcription is regulated by 4 enhancers localized in the first 10 kb of the mbp 5 0 -flanking sequence. One of the enhancers can enhance the transcription of both mbp and golli-mbp genes [51]. Although it has not been localized, the expression pattern of the MBP-CCL2 transgene that we observe is thus consistent with integration at a site(s) controlled by a Gollimbp enhancer.…”
Section: Discussionsupporting
confidence: 70%
“…In Sato's study, the two enhancers were cloned and examined individually, which could explain why enhancer activity in these tissues was not reported. The traditional view is that the interactions of multiple enhancers is mainly summative; however, there have also been reports of other more complex mechanisms such as the nonautonomous regulatory modules in the control of mbp in Drosophila . In the present study, a synergistic effect of Six1E1 and Six1E2 was observed, adding an additional example of enhancer synergy in vertebrates.…”
Section: Discussionsupporting
confidence: 49%
“…Specifically, the mbp and hprt loci are in different topological domains on different chromosomes, likely localize to distinct nuclear domains, recruit different epigenetic marks (Dixon et al, ; Dowen et al, ; Dowen and Young, ; Gibcus and Dekker, ; Jin et al, ) and generate unique non‐coding RNAs (ncRNAs); all with potential, and possibly competing, regulatory consequences (reviewed by Bonasio and Shiekhattar, ). To begin relating our findings with M3 reporter constructs to its function within the endogenous mbp locus, we evaluated the expression of an endogenous mbp allele deleted of M3 (Dib et al, ). This M3KO allele exposed the presence of additional regulatory components capable of driving mbp expression in oligodendrocytes at all ages (Dib et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The adjacent M2 lacks autonomous activity but augments M1. M3, the focus of this investigation, drives robust reporter gene expression in myelinating oligodendrocytes at all ages and when deleted from the endogenous locus, mbp and overlapping golli transcripts are markedly reduced (Dib et al, ). It also drives transient expression in myelin‐elaborating Schwann cells in juveniles.…”
Section: Introductionmentioning
confidence: 99%